The role of physical activity, stress, and lifestyle behaviors in adolescent mental health and well-being: A systematic review - Rahman, Dally; Edmizal, Eval; Denay, Naluri; Haryanto, Jeki; Dewi, Bunga Permata; Harahap, Asriandi (Department of Coaching, Faculty of Sports Science, Universitas Negeri Padang, Indonesia, 2025)
Problem: Young people often face mental health troubles such as strain, sleep disturbances, and low existence satisfaction. Even though many research has proven that bodily activity can enhance mental fitness, it's miles nevertheless doubtful how bodily activity works collectively with different life-style elements like strain, weight-reduction plan, and social media use. Purpose: This study aims to summarize the effects of physical activity and related lifestyle factors on adolescent mental health. Methods: This study utilized a systematic literature review approach, gathering and analyzing scientific articles on the effects of regular physical activity influence the risk of depression among adolescents. Articles were sourced from Scopus using search terms such as